Channel estimation for OFDM-IM systems - Aldırmaz Çolak, sultan; Başar, Ertuğrul; ACAR, YUSUF (My University, 2019)
Orthogonal frequency division multiplexing with index modulation (OFDM-IM) has been recently proposed to increase the spectral efficiency and improve the error performance of multicarrier communication systems. However, all the OFDM-IM systems assume that the perfect channel state information is available at the receiver. Nevertheless, channel estimation is a challenging problem in practical wireless communication systems for coherent detection at the receiver. In this paper, a novel method based on the pilot symbol-aided channel estimation technique is proposed and evaluated for OFDM-IM systems. Pilot symbols, which are placed equidistantly, allow the regeneration of the response of the channel so that pilot symbol spacing can fulfill the sampling theorem criterion. Our results shows that the low-pass interpolation and SPLINE techniques perform the best among all the channel estimation algorithms in terms of bit error rate and mean square error performance.
Keywords: Channel Estimation; Orthogonal Frequency Division Multiplexing; Indices Modulation; Frequency Selective Fading Channel; Interpolation